Dynamic Geomorphology of the Drumlin Coast of Southeast Cape Breton Island - Wang, Ying; Piper, D. J. W. (Atlantic Geology, 1982)
The southeastern coast of Cape Breton Island from Gabarus Bay to Framboise Cove has been investigated as a typical example of a drumlin coast. Landforms have been mapped from ground observations and air photographs. Time series of coastal profiles of both beaches and eroding drumlin cliffs have been measured. Nearshore sediment distribution has been mapped. An analysis has been made of wind and wave frequency and direction data. Four coastal segments are distinguished: (1) the south coast of Gabarus Bay has rock-cored drum-11ns separated by small barrier beaches; (2) the coast around Winging Point has a relatively stable depositional tombolo coast; (3) Fourchu Bay and Framboise Cove are developed in an area of thick till drumlins, and consist of barrier bars backed by lagoons and drumlins; and (4) the Fourchu Head and Red Cape are rocky coastlines from which all till has been removed by marine erosion, The geomorphologlcal evolution is a consequence of the initial drumlin landscape, the availability of a wide range of sediment sizes, and the type and intensity of marine erosion processes including the effects of transgression. Two types of coast are developed: a) in irregular hilly areas, where the till is thin and occurs in rock-cored drumlins; and b) in valley areas, where thick till drumlins are found. In each of these types, three stages of coastal development are distinguished. These represent the effect of differing rate of maturation, dependent on the configuration of drumlins and varying type and intensity of marine erosion.